THE MOBILE DERMATOLOGY PERSPECTIVES. MAIN TASKS - Yaroshenko, O. O. (Medical Informatics and Engineering, 2017)
Actual issues of mobile dermatology development are considered. It is emphasized that the mobile medicine should distinguish two major areas that provide mutual influence on each other. First is technology, devices, applications and services for the treatment and care of patients, the second are systems and devices for monitoring compliance with a healthy lifestyle (wellness) and fitness (fitness). There are highlighted the five most important tasks of mobile dermatology, corresponding to five cohorts of patients.